Extension of Learning Approach on the New Paradigm Curriculum for Elementary Level Teachers - Yudha Aprizani; Angga Taufan Dayu; Neneng Islamiah; Nurhasanah (UrbanGreen Central Media, 2022)
This article aimed to give the teachers an encouragement to be a vivid person to develop a learning approach namely project-based learning on the New Paradigma Curriculum for teacher of Elementary School. To develop an encouragement to the teacher. The practitioner tried to give an insight about educational system related to skills for students, the role of teacher, learning approach and characteristic of project based learning (PBL). To grasp the teachers’ comprehension to learning approach especially in PBL, the practitioner presented the diagram result of insight regarding on educational system. The result showed the teacher mostly have understood to the educational system. Indeed, partly, the other teachers were enough understanding to the educational system